An Analysis of Code Mixing by EFL Learners During English Speaking Practice: Bahasa Indonesia - Dayu Sabita Adiyati; Muhlisin Rasuki; Fitrotul Mufaridah (Empat Sembilan Publisher, 2025)
This study investigates the phenomenon of code mixing in English as a Foreign Language (EFL) classrooms, particularly focusing on students in a responsive speaking class at Universitas Muhammadiyah Jember. The research aims to identify the types of code mixing used, the contexts in which it occurs, and the reasons behind its usage. Utilizing a qualitative descriptive method, data were collected through classroom observations and semi-structured interviews. The analysis revealed that students frequently employ code mixing during group discussions and presentations. Four main types of code mixing were identified: word insertion, phrase insertion, hybrid forms, and clause mixing. The findings suggest that code mixing helps students articulate their ideas more effectively, especially when facing vocabulary limitations or feeling anxious. It also serves as a communicative strategy that supports language acquisition by boosting confidence and aiding understanding. This study concludes that code mixing is not merely a linguistic shortcut but a meaningful tool in the language learning process. The implications of this research underscore the pedagogical value of integrating code mixing into classroom practices to support EFL learners' speaking development.